Action Research Built on Uncertain Foundations: The internship and action-research in a graduate teaching degree - Loughland, Tony; Bowen, Margo (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
This paper analyses action research’s uncertain foundations in graduate teaching degrees. This analysis focuses on one Master of Teaching program in Australia, and is conducted by the program coordinator in partnership with a recent graduate of the program. Uncertainty is traced to the structural incoherence of the program that is created by the influence of disparate philosophies of teacher education. The philosophy and practice of the program is informed by both the scholar teacher and reflective practitioner models of teacher education. It is argued that these models are incommensurable and lead to a poor use of action research during the internship of the program. The action research would be more authentic if a phronetic model of teacher education underpinned the entire program rather than just the final internship. This phronetic model will remain an ideal because of the prevailing hegemony of neo-liberalism that supports a means-rationality associated with performing to the graduate standards rather than a values-rationality associated with developing a lifelong habit of phronetic practice.